Using Python Libraries To Visualize Math Problems (Eurasian Research Bulletin, 2024)
The article is devoted to the study of the use of Python libraries for visual demonstration of mathematical problems in the educational process. The paper analyzes the capabilities of various libraries, such as Matplotlib, Seaborn, Plotly, Bokeh, and PyQtGraph, in terms of their applicability to visualize various mathematical concepts